2020
DOI: 10.1177/0025817220971925
|View full text |Cite
|
Sign up to set email alerts
|

Corruption and strengthening anti-corruption efforts in healthcare during the pandemic of Covid-19

Abstract: The Covid-19 pandemic has created the opportunity for corruption to flourish in healthcare sectors around the world. Challenges include misuse and mismanagement of resources and corruption, which require scrutiny and attention. This article deals with such corruption during the pandemic, involving public procurement of goods and services for the treatment of diseases, falsification of public contracts and kickbacks, embezzlement of healthcare funds, opacity in governance, misuse of power, nepotism and favourit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
37
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 3 publications
0
37
0
1
Order By: Relevance
“…COVID-19 has provided a new avenue for corruption in the health care sectors around the globe. In a theoretical study, Teremetskyi et al ( 2020 ) pointed out the recent challenges in the health division, which require inspection and devotion. These challenges are based on corrupt practices such as misuse of resources, deception in public agreements, mismanagement of funds, embezzlement of medical-related equipment, and so on.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…COVID-19 has provided a new avenue for corruption in the health care sectors around the globe. In a theoretical study, Teremetskyi et al ( 2020 ) pointed out the recent challenges in the health division, which require inspection and devotion. These challenges are based on corrupt practices such as misuse of resources, deception in public agreements, mismanagement of funds, embezzlement of medical-related equipment, and so on.…”
Section: Introductionmentioning
confidence: 99%
“…By analyzing the table and the prevailing literature, a few gaps in the earlier studies can be identified as follows: Most of the articles only discussed either one or a maximum of two the aspects of corruption, the environment, and the COVID-19 pandemic. For example, Malta et al ( 2021 ) discussed the COVID-19 pandemic; Olamide and Maredza ( 2021 ) and Goel et al ( 2021 ) discussed corruption and the COVID-19 pandemic; Chukwu and Nnogo ( 2021 ) and Teremetskyi et al ( 2020 ) discussed the COVID-19 pandemic and health care services, etc. To the best of our knowledge, to date, none of the studies have presented the unique cycle of corruption, the environment, and the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…3 Government transparency in decision-making has been described as a major problem in response efforts worldwide, 4 together with weak regulations and accountability mechanisms and low wages in the heath sector. 5 In countries such as the United Kingdom, a National Health Service official was found selling PPE on the side, and the U.S. administration paid extraordinary prices to third-party vendors. 6 …”
Section: Introductionmentioning
confidence: 99%
“…In the resultant exclusive environment, the sense of duty and obligation among public servants have often made the difference. However, challenging circumstances, including COVID-19’s impact on public sector processes, have exposed vulnerabilities, including tendencies toward mismangement and misue of resources (Teremetskyi et al, 2021 ). This demonstrates a need for additional attention in the literature, as corruption can turn hazards into disasters (Escaleras & Register, 2016 ).…”
Section: Introductionmentioning
confidence: 99%